2015
DOI: 10.1097/qai.0000000000000411
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Second-Line Antiretroviral Therapy Among People Living With HIV/AIDS in Asia

Abstract: Background Roughly 4% of the 1.25 million patients on antiretroviral therapy (ART) in Asia are using second-line therapy. To maximize patient benefit and regional resources it is important to optimize the timing of second-line ART initiation and use the most effective compounds available. Methods HIV positive patients enrolled in the TREAT Asia HIV Observational Database who had used second-line ART for ≥6 months were included. ART use and rates and predictors of second-line treatment failure were evaluated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 36 publications
6
28
2
Order By: Relevance
“…25 34 35 However, the incidence of failure found by this study is lower than a multicentred study conducted in Asia and Africa, which found an overall incidence of 195 per 1000 person-years 36. The reason for this might be due to the difference in follow-up periods.…”
Section: Discussioncontrasting
confidence: 79%
“…25 34 35 However, the incidence of failure found by this study is lower than a multicentred study conducted in Asia and Africa, which found an overall incidence of 195 per 1000 person-years 36. The reason for this might be due to the difference in follow-up periods.…”
Section: Discussioncontrasting
confidence: 79%
“…In addition, the predictive power of patient outcomes on ART-1 for the most serious adverse events, even after changes in therapy, highlights the potential benefit of focusing resources to enhance monitoring of those patients experiencing blunted CD4 response, and of course, toxicities while on their initial regimen. Though this may seem an obvious course of action and is essentially in line with recent recommendations for first line therapy by the United States (40) and the World Health Organization (41), the execution and logistics involved are not trivial in resource-limited settings (42). Further, despite the implication of these findings that prescription of an initial regimen with maximal antiviral activity and a low side-effect/toxicity profile would be the surest bulwark against accelerated disease progression, again, the plausibility of implementing this practice is greatly dependent on the most readily available antiretroviral agents (43,44).…”
Section: Discussionsupporting
confidence: 60%
“…Current WHO guidelines recommend use of a ritonavir‐boosted protease inhibitor (PI) in combination with dual NRTIs after failure on a first line NNRTI‐based regimen, which is widely practiced in Asia . A prior TREAT Asia HIV Observational Database (TAHOD) study reported that among 302 patients with first‐line treatment failure, 73% switched to a dual NRTI plus boosted PI regimen . Use of ritonavir‐boosted lopinavir (LPV/r) or atazanavir (ATV/r) compromised the majority of boosted PI use beyond 2006 in this cohort .…”
Section: Introductionmentioning
confidence: 91%
“…A prior TREAT Asia HIV Observational Database (TAHOD) study reported that among 302 patients with first‐line treatment failure, 73% switched to a dual NRTI plus boosted PI regimen . Use of ritonavir‐boosted lopinavir (LPV/r) or atazanavir (ATV/r) compromised the majority of boosted PI use beyond 2006 in this cohort . Most commonly used NRTIs for second‐line treatment were lamivudine/emtricitabine (3TC/FTC), tenofovir (TDF) and zidovudine (AZT), accounting for 76.5%, 44.4% and 32.1% of all patients respectively .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation